2015
DOI: 10.1038/nrcardio.2015.137
|View full text |Cite
|
Sign up to set email alerts
|

New medical therapies for heart failure

Abstract: Heart failure (HF) can rightfully be called the epidemic of the 21(st) century. Historically, the only available medical treatment options for HF have been diuretics and digoxin, but the capacity of these agents to alter outcomes has been brought into question by the scrutiny of modern clinical trials. In the past 4 decades, neurohormonal blockers have been introduced into clinical practice, leading to marked reductions in morbidity and mortality in chronic HF with reduced left ventricular ejection fraction (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 150 publications
0
27
0
Order By: Relevance
“…Indeed, it has recently been reported that Sacubitril/Valsartan has the potential to lower high-sensitivity troponin T (hs-TnT) levels, a biomarker for myocyte injury and myocardial cell death, in HF patients. 29, 30 Taking this into account, our analyses now provide a new perspective on relevant, though previously unknown, MoA.…”
Section: Discussionmentioning
confidence: 89%
“…Indeed, it has recently been reported that Sacubitril/Valsartan has the potential to lower high-sensitivity troponin T (hs-TnT) levels, a biomarker for myocyte injury and myocardial cell death, in HF patients. 29, 30 Taking this into account, our analyses now provide a new perspective on relevant, though previously unknown, MoA.…”
Section: Discussionmentioning
confidence: 89%
“…Potential pharmacological agents have been identified that target pathophysiological features of the failing heart. Many new medical therapies of heart failure have been extensively reviewed elsewhere (see [15, 16]). Here we focus on two recent therapies that have had positive results from phase II and/or phase III clinical trials.…”
Section: New Pharmacological Agents Targeting Pathophysiological Featmentioning
confidence: 99%
“…Contrary to expectations, recent clinical studies have failed to demonstrate the benefits offered by drugs effective in HFrEF to HFpEF patients (16, 2123). Thus, HFpEF is one of the largest unmet needs in cardiovascular medicine, and there is a substantial requirement for new therapeutic approaches and strategies that target mechanisms specific for HFpEF (16).…”
Section: Introductionmentioning
confidence: 80%